Natural Disaster, Local Knowledge, and Local Policy in a Small City in Southeast Sulawesi, Indonesia - Idaman Idaman; Handrawan Handrawan; Indra Rahayu Setiawati; Irwansyah; Nisa Nasyra Rezki (Journal of Law, Social Science and Management, 2025)
Background: Konawe Selatan is one of the regions with a high intensity of natural disasters in Southeast Sulawesi. From time to time, natural disasters in Konawe Selatan seem to have become a "daily routine" for the community. The local knowledge system and regional government policies need to be continuously promoted so that they can become a model for disaster management in this area. Objective: This paper explores the significance of integrating local knowledge with local governmental policies in natural disaster management in a small city di SE Sulawesi Indonesia. It examines case studies where such integration has proven successful, highlights the challenges faced in aligning traditional wisdom with modern governance structures, and suggests strategies for effective collaboration Method: The method used in this research is descriptive qualitative, utilizing data from surveys and interviews. Surveys were conducted in several coastal areas of Konawe Selatan that are often affected by natural disasters. Interviews were conducted with several informants to explore a disaster management model based on local wisdom. Result: Research results show that local communities in coastal areas have utilized local wisdom in facing natural disasters, including the ability to read natural signs. When a natural disaster is about to occur. Local wisdom in disaster management needs to be supported by the local government, especially in collaboration with the regional disaster management agency to formulate various policies and practices for managing natural disasters in disaster-affected areas. Discussion: The coastal areas in South Konawe, which are largely inhabited by the Tolaki, Bugis, and Bajo communities, have long had experience dealing with natural disasters. This experience has enabled them to survive until now. Various traditions or local wisdom are used as efforts to anticipate natural disasters, such as the ritual of tolak bala, mosehe, and the ability to read natural signs. Conclusion: The local knowledge system related to natural disasters has proven to be resilient until now and has become one of the effective means for handling natural disasters. At this point, the local government policy of Konawe Selatan needs to adapt this local wisdom. So far, there have been several regulations issued by the local government of Konawe Selatan in managing natural disasters. And it seems to have been quite effective in reducing the number of casualties and property damage. Keywords: Local Knowledge, Local Government, Coastal Areas, Natural Disaster